2023
DOI: 10.3390/vaccines11040864
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Recombinant Proteins S1/N and RBD/N as Potential Vaccine Candidates

Abstract: Despite all successful efforts to develop a COVID-19 vaccine, the need to evaluate alternative antigens to produce next-generation vaccines is imperative to target emerging variants. Thus, the second generation of COVID-19 vaccines employ more than one antigen from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) to induce an effective and lasting immune response. Here, we analyzed the combination of two SARS-CoV-2 viral antigens that could elicit a more durable immune response in both T- and B-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…For this purpose several studies have tested SARS-CoV-2 candidate vaccines that include other structural proteins (mostly the N protein) in adenoviral vectors [19][29], modified vaccinia Ankara vectors [30][31], subunit protein vaccine candidate [32][33] and others [34]. These studies showed protective efficacy, T-cell and humoral response caused by vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose several studies have tested SARS-CoV-2 candidate vaccines that include other structural proteins (mostly the N protein) in adenoviral vectors [19][29], modified vaccinia Ankara vectors [30][31], subunit protein vaccine candidate [32][33] and others [34]. These studies showed protective efficacy, T-cell and humoral response caused by vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, several studies have tested SARS-CoV-2 candidate vaccines that include other structural proteins (mostly the N protein) in the adenoviral vectors [20,36], modified vaccinia Ankara vectors [37,38], subunit protein vaccine candidates [39,40], and others [41]. These studies have demonstrated the protective efficacy of and the T-cell and humoral responses induced by vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Immunization with S1 + N or RBD + N induced IgG1, IgG2, and neutralizing activity, and production of IFN- γ , TNF- α , and IL-2 with higher responses was observed in combination with the N protein. Moreover, sera from the immunized mice showed cross-reactivity with RBD from Alpha and Beta VOCs [ 84 ]. A combination of spike and nucleocapsid proteins using a conventional formulation with aluminum hydroxide, lipids, or other adjuvants has shown induction of humoral and cellular response [ 85 , 86 , 87 , 88 , 89 ].…”
Section: The Potential Use Of Nucleocapsid As Vaccine Antigenmentioning
confidence: 99%